Macroporous polymers : production properties and biotechnological/biomedical applications - Mattiasson, Bo, 1945-; Kumar, Ashok, 1963-; Galaev, Igor. (Boca Raton, FL. : CRC Press, 2010)
Macroporous polymers are rapidly becoming the material of choice for many tissue engineering, bioseparation, and bioprocessing applications. Presented in a systematic way, this book addresses the production, characterization, and application of these polymers.
Production of macroporous polymeric materials by phase separation polymerization / Oguz Okay -- Production and properties of cryogels by radical polymerization / Fatima M. Plieva, Igor Yu. Galaev, and Bo Mattiasson -- Macroporous polymer scaffolds through leaching processes / Michael C. Hacker, Kristina Ambrosch, and Michaela Schulz-Siegmun -- Production and properties of poly(vinyl alcohol) cryogels : recent developments / Mar C. Gutirez ... [et al.] -- Preparation of polylactide scaffolds / Ming-Hua Ho ... [et al.] -- Macroporous polysaccharide gels / Fatima M. Plieva, Igor Yu. Galaev, and Bo Mattiasson -- Superporous agarose gels : production, properties, and applications / Per-Erik Gustavsson, Peter Tiainen, and Per-Olof Larsson -- Fast-responsive macroporous hydrogels / Hossein Omidian and Kinam Park -- Characterization of macroporous gels / Irina N. Savina ... [et al.].
Includes bibliographical references and index.
Keywords: Polymers; Porous materials